Analysis of the Accuracy of Uncertainty Noise Measurement - PRZYSUCHA, Bartosz; BATKO, Wojciech; SZELĄG, Agata (Archives of Acoustics, 2015)
The paper formulates some objections to the results of the evaluation of uncertainty in noise measurement which are presented in two standards: PN-ISO 9612 (2004) and DIN 45 641 (1990). In particular, it focuses on an approximation of the equivalent sound level by a function which depends on the arithmetic average of sound levels. Depending on the nature of a random sample the exact value of the equivalent sound level may be significantly different from the approximate one, which might influence on the erroneous estimation of the uncertainty of noise indicators. The article presents an analysis of this problem and the adequacy of the solution depending on the type of the random sample.